(untitled) (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2021)
Purpose of this study was to development of accounting conservatism measuring instruments used in by experts. The method used is a descriptive analysis method. Results showed that measuring instruments commonly used in accounting conservatism are net assets measurement, earning and accruals measurement, and earning/stock return relation measurement. This study gives impacts on contribute to the development of accounting conservatism measurement tools.